Prevalence of Depression and Use of Antidepressant in Basic Medical Sciences Students of Nepalgunj Medical College, Chisapani, Nepal - Dhami, Dabal B.; Singh, Ankita; Shah, Gaurav Jung (Journal of Nepalgunj Medical College, 2018)
Introduction: According to WHO, depression would be the second-most prevalent condition worldwide by 2020. The prevalence of depression is increasing in medical colleges because of stressful, competitive environment, long hours of trainings and studying. It is important for medical educators or teacher to know the magnitude of depression in students and factors causing it. The present study was carried to assess the prevalence of depression, use of antidepressant and to find out their stressors among preclinical students of Nepalgunj Medical College, Chisapani, Nepal. Aims and objective: To assess the prevalence of depression, use of antidepressant and to find out their most common stressor among preclinical students Materials and methods: The descriptive cross sectional study was carried in preclinical students of Nepalgunj Medical College, Chisapani, Nepal, The data was collected with questionnaires which comprised of personal data (age, sex, year of study, religion and home country) and Zung Depression Inventory scale was used to rate the depression. Results: Among 218 students, the prevalence of depression was 24.3%. Male students are highly depressed (16.5%) then female (7.8%). First year student are more depressed (26.5%) then second year (22.4%). The depression score of the preclinical medical student was 44.67± 5.68 (mean ±SD). Majority of the students (>50%) found on academic stress and 3.6% of the total students were on antidepressants Conclusion: As the prevalence of depression is high in medical students there is need for the counselling services to the students in the medical college to control this morbidity.